Determination of the dependence of the structure of Zn-Al layered double hydroxides, as a matrix for functional anions intercalation, on synthesis conditions - Kovalenko, Vadym; Borysenko, Anastasiia; Kotok, Valerii; Nafeev, Rovil; Verbitskiy, Volodymyr; Melnyk, Olena (Eastern-European Journal of Enterprise Technologies, 2022)
Layered double hydroxides, especially Zn-Al, are valuable matrices for intercalation with various functional anions: dyes, medicines, food additives, etc. For the purposeful development and optimization of the technology for the synthesis of Zn-Al hydroxides intercalated with functional anions, the phase composition and crystal structure of Zn-Al nitrate layered double hydroxide samples (Zn:Al=4:1) synthesized at solution flow rates of 0.8 and 1.6 l/h, pH=7, 8, 9, 10 and t=10, 20, 30, 40, 50 and 60 °С were studied. XRD showed that all samples synthesized at different temperatures, pH, and solution flow rates were Zn-Al layered double hydroxides with an α-Zn(OH)2 crystal lattice of medium crystallinity, with an admixture of an oxide phase with a ZnO lattice. Three sections of the dependence of the crystallite size of the sample on the synthesis temperature were distinguished: 10–20 °C, 30–50 °C, and 60 °C, within which an increase in temperature led to an increase in crystallinity. A hypothesis was put forward about a change in the mechanism or kinetics of LDH formation at temperatures of 30 °C and 60 °C. An increase in the pH of the synthesis and the flow rate of solutions led to an increase in crystallinity. A retrospective comparative analysis of the phase composition and crystal structure of Zn-Al-nitrate and Zn-Al-tripolyphosphate (tartrazine or Orange Yellow S) LDH samples was carried out. It was found that the use of large and multi-charged functional anions caused significant adsorption on precipitate nuclei and difficult intercalation. As a result, low crystallinity was formed (Tartrazine anion) or a significant part of LDH was decomposed to oxide (tripolyphosphate and Orange Yellow S anions).